Groundwater Vulnerability Assessment and Mapping : IAH-Selected Papers, volume 11. - Witkowski, Andrzej J. (Hydrogeology (International Association of Hydrogeologists), 2014)
This volume presents the contemporary issues surrounding groundwater pollution risk assessment and the application of vulnerability and risk assessment maps for the effective protection and management of aquifers. Numerous new and improved approaches to intrinsic and specific vulnerability assessment (modified DRASTIC, GOD, VULK, VURAAS) are described, some coupled with geophysical and hydrological surveys and hydrodynamic and transport modelling. Widespread use is made of GIS format.